TINJAUAN HUKUM TENTANG PEMILIHAN UMUM PRESIDEN PASCA REFORMASI DIKAITKAN DENGAN TEORI DEMOKRASI - Elwidarifa Marwenny; Sry Wahyuni; Helfira Citra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The form of the Indonesian Government is democracy. Therefore, the MPR which consists of the DPR and DPD as well as the President is elected through a general election. As stated by Juan Linz, G. Bingham Powell, Jr., and Robert Dahl. Almarhum Prof. Dr. Affan Gaffar, MA, one of the indicators of the implementation of a democratic state is the general election. Since the amendment to the Fundamental constituion 1945, Indonesia has held four presidential elections through direct democracy, notably in 2004, 2009, 2014, and the most recent presidential election in 2019, which was held simultaneously with the legislative elections. In the implementation of the presidential election, there are various problems that contribute to the perception that the general election is nothing more than ceremonial so the Indonesian election is not trusted by the public as a realization of democracy. According to this thing condition, we know that fraud appears to be unavoidable in the holding of the election in Indonesia, particularly the presidential election, which is conducted by the highest state organizer so that the writer wants to knowwhether the presidential election after the amendment has brought the spirit of democracy or not? and which presidential election is the most democratic after the amendment to the fundamental constitution 1945? To answer these questions, a qualitative method was used with a normative juridical approach, so that it can be concluded that normatively, the presidential election has carried democratic values and it is hard to judge the most democratic presidential election in Indonesia only by using the indicator of the law..Keywords: presidensial election, democracy, law